Effect of Work Discipline on Employee Performance Mediated Job Satisfaction at RSIA Melinda - Ari Aprian Ferdiansyah; Nurul Hermina (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
This study aims to determine how the effect of work discipline on the performance of RSIA Melinda employees mediated by job satisfaction. The research method used in this research is descriptive and verification method. The population in this study were employees of RSIA Melinda. The sampling method in this study uses "total sampling", which uses all members of the population, namely 63 employees. While inferential statistics are used in this study with the method of path analysis. The results showed that discipline had a positive and significant effect on job satisfaction; Work discipline has no significant effect on employee performance; Job satisfaction has a positive and significant effect on employee performance; Job satisfaction is able to mediate the relationship between discipline and performance.